(untitled) (Journal of Lithic Studies, 2016)
The Middle Palaeolithic site of Lagoa do Bando is an open air site in a lacustrian context located at 570 m a.s.l. in the municipality of Mação in the center of Portugal. The site was discovered in 2011, during an emergency excavation, and resulted on the recovery of a Middle Palaeolithic lithic assemblage mainly composed of fine grained quartzite implements of expedient, discoid and Levallois technology. Use wear analysis was conducted on 41 artifacts formed through discoid and Levallois technology. Twenty one of these artifacts revealed use wear traces. Ten of them show traces of wood work, five have traces of butchering activities, three present traces of meat processing and two present undetermined traces. The site is located at an atypically high elevation for an open air site and there is evidence of a high rate of woodworking activity, rare in the Middle Palaeolithic occupations. The woodworking activities are possibly linked to the exploitation of woody local resources (maybe for the construction of hunting blinds) and not only with to the manufacture and maintenance of spears and shafts. These results converge with the interpretation of this site as a temporary hunting site integrated in a complex pattern of occupation of the area between the river valleys and the top of low mountains.